The T-Cell Response to Lipid Antigens of Mycobacterium tuberculosis - De Libero, Gennaro; Mori, Lucia (Frontiers in Immunology, 2014)
T cells recognize lipid antigens presented by dedicated antigen presenting molecules that belong to the CD1 family. This review discusses the structural properties of CD1 molecules, the nature of mycobacterial lipid antigens, and the phenotypic and functional properties of T cells recognizing mycobacterial lipids. In humans the 5 different CD1 genes encode structurally similar glycoproteins that recycle in and thus survey different cellular endosomal compartments. The structure of the CD1 lipid binding pockets, their mode of intracellular recycling and the type of CD1-expressing antigen presenting cells all contribute to diversify lipid immunogenicity and presentation to T cells. Mycobacteria produce a large variety of lipids, which form stable complexes with CD1 molecules and stimulate specific T cells. The structures of antigenic lipids may be greatly different from each other and each lipid may induce unique T cells capable of discriminating small lipid structural changes. The important functions of some lipid antigens within mycobacterial cells prevent the generation of negative mutants capable of escaping this type of immune response. T cells specific for lipid antigens are stimulated in Tuberculosis and exert protective functions. The mechanisms of antigen recognition, the type of effector functions and the mode of lipid-specific T cell priming are discussed, emphasizing recent evidence of the roles of lipid-specific T cells in Tuberculosis.